Perbedaan kadar seng serum dan kadar c-reactive protein pada anak balita dengan kadar serum retinol normal dan tidak normal - Kadek Tresna Adhi; Bambang Wirjatmadi; Meriyana Adriani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Vitamin A Defciency (VAD) is one of the major nutritional problem, and many occur in developing countries. VAD occurs when serum retinol concentration <20 tg / dl (0.07 μmol / L). Serum retinol levels will decrease during the acute phase response (elevated CRP) and also caused by zinc defciency. This interaction causes inhibition of linear growth.Objective: The objective of this research is to study the differences in levels of serum zinc and CRP levels in infants and children with normal serum retinol (≥ 20 tg / dl) and abnormal (≥ 20 tg / dl) in the Village of Mojo, District Gubeng, Surabaya.Method: Results of the analysis was divided into two categories: 1) normal serum retinol (≥ 20 tg / dl), and 2) abnormal levels of serum retinol (<20 tg / dl). For serum zinc levels, laboratory examination was performed by AAS method (Atomic Absorption Spectrophotometry). CRP level was done by agglutination test method (CRP latex) with results in the form of semi-quantitative analysis. The collection of data includes the frequency characteristic of children and the sick for a month with interviews conducted using a questionnaire. Consumption data using dietetic (2x24-hour recall). Analysis of data using two independent samples t test.Results: The results showed that there was no difference in characteristics, levels of consumption and CRP levels of children under fve (p> 0.05). While there are differences in the frequency of pain and zinc (p <0.05).Conclusion: No difference in zinc levels in both groups, whereas CRP levels did not show different results. It was recommended that further research on the interaction of research results with linear growth as well as environmental factors and personal hygiene to prevent infection that can affect serum retinol.